2017
DOI: 10.1016/j.ccell.2017.02.018
|View full text |Cite|
|
Sign up to set email alerts
|

O 2 ⋅− and H 2 O 2 -Mediated Disruption of Fe Metabolism Causes the Differential Susceptibility of NSCLC and GBM Cancer Cells to Pharmacological Ascorbate

Abstract: Summary Pharmacological ascorbate has been proposed as a potential anti-cancer agent when combined with radiation and chemotherapy. The anti-cancer effects of ascorbate are hypothesized to involve the autoxidation of ascorbate leading to increased steady-state levels of H2O2; however, the mechanism(s) for cancer cell-selective toxicity remain unknown. The current study shows that alterations in cancer cell mitochondrial oxidative metabolism resulting in increased levels of O2•− and H2O2 are capable of disrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
396
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(413 citation statements)
references
References 70 publications
16
396
0
1
Order By: Relevance
“…In cancerous cells, ROS acts as an apoptosis-promoting agent and the excess of antioxidants can block these cancer-preventive mechanisms and develop cancer (Salganik 2001). Recently Schoenfeld et al (2017), demonstrated that the alterations of redox-active iron metabolisms in cancer cells in comparison to normal cells are responsible for the specific activity of ascorbic acid (antioxidant agent) against nonsmall-cell lung cancer (NSCLC) and glioblastoma (GBM) cells. It is understood from this example that an excess of antioxidants can also kill cancer cells but by using a different mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In cancerous cells, ROS acts as an apoptosis-promoting agent and the excess of antioxidants can block these cancer-preventive mechanisms and develop cancer (Salganik 2001). Recently Schoenfeld et al (2017), demonstrated that the alterations of redox-active iron metabolisms in cancer cells in comparison to normal cells are responsible for the specific activity of ascorbic acid (antioxidant agent) against nonsmall-cell lung cancer (NSCLC) and glioblastoma (GBM) cells. It is understood from this example that an excess of antioxidants can also kill cancer cells but by using a different mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…show positive outcomes if cancer is treated with high concentrations of the antioxidant vitamin C (Schoenfeld et al, 2017).…”
Section: Nox4-derived H 2 O 2 Is Essential To Maintain Cellular Homeomentioning
confidence: 99%
“…High doses of intravenous vitamin C were found to significantly reduced levels of prostate-specific antigen (PSA), an appreciated serum biomarker for prostate cancer[28]. Pro-oxidant effects of DHA have also been explored in non-small cell lung cancer (NSCLC) and glioblastoma (GBM), where H 2 O 2 induced by the extracellular conversion of ascorbic acid to DHA, selectively disrupted iron metabolism in cancer cells, leading to cytotoxic effects, and its efficacy has been demonstrated in preclinical and clinical trials when paired with standard radiation and chemotherapy regiments[29]. …”
Section: Introductionmentioning
confidence: 99%